Morphological characterization of sweet and sour cherry cultivars in a germplasm bank at Portugal - Rodrigues, Luciano (2011)
Nine sweet cherry and eight sour cherry varieties located in a germplasm bank at Fundauo, Portugal, were studied from the viewpoint of characterization. Most of them were autochthonous cultivars that have a high risk of extinction since at the present they are markedly minor varieties. Morphological characteristics were evaluated in different organs: crown and trunk of the trees, leaves, flowers and fruits, over a three consecutive years period. Statistical analyses were carried out in order to detect similarities between cultivars as well as the existence of synonymies. Qualitative characteristics of the fruits were scored in order to carry out the multivariate analysis. A dendrogram of the evaluated characters shows the marked differentiation between sour and sweet cherries and suggests the existing synonymies. Conservation of the autochthonous cultivars in the future is highly recommended.